Microbiological study of etiological pathogen in early infection of open fracture in orthopedics - Tai, Ken Meng; Sulong, Ahmad Fadzli; Mohd Yusof, Nazri (Malaysian Orthopaedic Association, 2019)
PURPOSE: To evaluate the susceptibility of microorganism causing early infection in open fractures to current antibiotic prophylaxis and determine contributing factors towards development of resistance. METHODS: A total of 110 cases of open fractures were selected in this study. They underwent routine debridement and C&S were followed up. Risk factors to antibiotic resistance were identified. RESULTS: Admission to ICU, blood transfusion, antibiotic regime and duration, fracture grade, injury severity score and duration of admission were significantly associated with resistance of microorganism. There was Gram-negative predominance of 65.9%. The overall resistance to Cefuroxime was 68.6% and 36.9% to Gentamicin. Staphyloccoccus aureus and MRSA were the commonest Gram-positive while Pseudomonas and Acinetobacter Gram-negative. DISCUSSIONS: Resistance in open fracture is not well established unlike rate of infection. Previous studies reported predominant Gram-postive microorganisms which form the basis of prophylactic antibiotics1 . Hannigan et al. reported increasing multi-drug resistance bacterias in open fractures2 . Carsenti-Etesse et al. reported resistance was influenced by type and duration of antibiotics while others have described various other factors3 . CONCLUSION: The high resistance of microorganisms and shift to predominantly Gram-negative microorganisms is alarming. Further measures are needed to achieve optimal outcome. REFERENCES: 1. Gustilo, R.B., (1971). Management of open fractures. An analysis of 673 cases. Minnesota Medicine, 54(3), pp.185–189 2. Hannigan, G.D. et al., 2014. Cultureindependent pilot study of microbiota colonizing open fractures and association. Journal of Orthopaedic Research, 32(